Committee on World Food Security (CFS) Members endorse new Voluntary Guidelines on Food Systems and Nutrition, which will support countries in efforts to eradicate all forms of hunger and malnutrition - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The Voluntary Guidelines provide guidance, mainly to governments, on effective policies, investments and institutional arrangements that address malnutrition in all its forms through a comprehensive food systems approach.